2017
DOI: 10.18251/ijme.v19i1.1387
|View full text |Cite
|
Sign up to set email alerts
|

Critical Autoethnography, Education, and a Call for Forgiveness

Abstract: If critical autoethnographers identify and attempt to remedy personal/cultural offenses, then they should also discuss how to live with individualsthemselves included-who have been complicit in and/or committed these offenses. One way critical autoethnographers can do so is through the concept of forgiveness. In this article, I first describe characteristics of forgiveness and establish relationships between forgiveness and critical autoethnography. I then offer three brief critical autoethnographies, each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…suggested that critical autoethnography invokes "clear and powerful theoretical frameworks for understanding how stories help us write into or become the change we seek in the world" (p. 1). It may also offer an approach to deal reflexively with personal offenses that one may have committed (Adams, 2017). As a research and pedagogical strategy, critical autoethnography's imperative towards reflexivity enables the strategic use of personal narratives to engage with broader social justice issues at play in society (Reed-Danahay, 2017), as is the case that I report on in this paper.…”
Section: A Methodological Notementioning
confidence: 99%
“…suggested that critical autoethnography invokes "clear and powerful theoretical frameworks for understanding how stories help us write into or become the change we seek in the world" (p. 1). It may also offer an approach to deal reflexively with personal offenses that one may have committed (Adams, 2017). As a research and pedagogical strategy, critical autoethnography's imperative towards reflexivity enables the strategic use of personal narratives to engage with broader social justice issues at play in society (Reed-Danahay, 2017), as is the case that I report on in this paper.…”
Section: A Methodological Notementioning
confidence: 99%
“…Autoethnography is an approach to research and writing that seeks to describe and systematically analyze personal experience in order to understand cultural experience [32]. Autoethnography is aimed at identifying manifestations of power and privilege in everyday practices that should -and should not -exist [33]. Combining ethnography, biography, and self-analysis, autoethnography as a research method utilizes data about self and context to gain understanding of the connectivity between self and others within the same context [34].…”
Section: Methodsmentioning
confidence: 99%
“…Autoethnography was developed using postmodern sensibilities that "resist colonialist, sterile research impulses of authoritatively entering a culture, exploiting cultural members, and then recklessly leaving to write about the culture for monetary and/or professional gain" (Ellis et al, 2011: 247). This approach draws upon feminist theory and relational ethics to provide an accountability structure for autoethnographers who not only implicate themselves in their work but also surrounding institutions, communities, and intimate others (Adams, 2006;Ellis et al, 2011).…”
Section: A Brief Overview Of Autoethnographymentioning
confidence: 99%